Employees feedback on office workspace configuration in Public Higher Learning Institution - S.N. Kamaruzzaman,; E.M.A. Zawawi, (Penerbit UKM, 2010)
Space planning is an integral part because without proper planning, a good workspace configuration could not be achieved. Models and concepts that were reviewed could be an essential guide in planning process. Attention should be put on the core elements as the workspace is design for a purpose. If the design fails and the users were not satisfied, then the configuration could be considered fail as a whole where it cannot help the organizations reach their goals and objectives. Therefore, a thorough understanding of the planning process will be very useful to achieve the ideal workspace configuration. This research aims to study and analyze workspace configuration that has been implemented in offices on public higher learning institution in Malaysia. Based on the observation and the data gathered, the workers comfort and satisfaction level are very important as these two aspects would result in the overall productivity of the organization. The workspace in offices should be reconfigured according to the people, location, design and worker’s work style. These factors play an important role in shaping a good working environment with a proper workspace configuration. Questionnaires were distributed to each case study and feedbacks from the respondents were gathered. The questions enquired on their perception and the satisfactory level on their current workstation. Case studies will provide essential background information reflecting the office workspace configuration in today’s offices. This study believes to be valuable in identifying the criteria and key factors affecting the satisfaction level of the workers. Analysing data will provide the first indication of how well the space configuration practice is performing and helped pin point problem areas within office workspace. It is anticipated that this study would contribute to the development of a better office workspace by improving quality and value of workspace configuration of public higher learning institution in Malaysia.